Boosting Students’ Reading Comprehension Using REAP Method - Kurnia, Rafika; Hidayat, Nur; Kustantinah, Indri (Educalingua Journal, 2024)
This research highlights the vital role of English reading skills in students'' literacy and comprehension. Implementing the REAP technique enhances reading comprehension by fostering interactive study-reading methods. Addressing issues like lack of interest, it offers a promising approach to enhance English education at SMA Institut Indonesia Semarang, as evidenced by its effectiveness in improving 11th-grade students' reading abilities. This quasi pre-experimental research employs a one-group pretest-posttest design, chosen for its convenience in obtaining internal samples. Class XI-3 was selected based on teacher recommendations. With 31 students, the study adopts a quantitative approach, focusing on reading comprehension tests administered before and after classroom instruction using multiple-choice questions as the assessment instrument. The pre-test, revealing a range of scores from 44 to 76 with a mean of 64.12, highlights initial reading struggles. Post-treatment, the post-test exhibits diverse scores, averaging 76.38, indicating improvement. The REAP method effectively enhances comprehension, as evidenced by the significant score increase from pre-test (64.12) to post-test (76.38), validating its efficacy. The research findings reveal a notable improvement in students'' reading comprehension abilities following the implementation of the REAP Method, despite initial unsatisfactory grades. The approach effectively enhances students' understanding and analytical skills, demonstrating its high effectiveness as a reading comprehension strategy. Overall, the significant difference between pre-test and post-test scores underscores the success of the REAP Method in advancing students' reading comprehension abilities, affirming its efficacy as a teaching approach